Single-Resistance-Controlled Sinusoidal Oscillator Using Single VD-DIBA - K. L. Pushkar; D. R. Bhaskar; Dinesh Prasad (Active and Passive Electronic Components)
This paper presents a new single-resistance-controlled sinusoidal oscillator (SRCO). The proposed oscillator employs only one voltage differencing differential input buffered amplifier (VD-DIBA), two resistors, and two grounded capacitors. The proposed configuration offers the following advantageous features: (i) independent control of condition of oscillation and frequency of oscillation, (ii) low active and passive sensitivities, and (iii) a very good frequency stability. The validity of the proposed SRCO has been established by SPICE simulations using 0.35 μm MIETEC technology.